Somatic mutation in the HLA‐B gene of a patient with acute myelogenous leukaemia. (14th June 2016) - Planelles, D.; Balas, A.; Gil, C.; Muñoz, C.; Rodríguez‐Cebriá, M.; Vicario, J. L.
Abstract: In this report we describe a case of somatic mutation in the HLA‐B gene in the tumour cells of a patient with acute myelogenous leukaemia (AML). Routine human leukocyte antigen (HLA) typing of patient by serology and molecular methodologies rendered discrepant results regarding the expression of a B*15:01 antigen. Sequencing‐based typing of a patient's sample including a very high percentage of blast cells revealed the presence of one nucleotide insertion at exon 3, position 440, codon 123. This insertion resulted in a reading frame shift and a premature stop codon at position 152. The mutation was absent in a sample obtained when the patient was in remission. This case report points out the relevance of the sample source for HLA typing in patients with haematological malignancies.